Application of chemometry for identification of the source of plutonium. (1st January 2011) - Alamelu, Devanathan; Aggarwal, Suresh K.
Isotope correlations and chemometry using Principal Component Analysis (PCA) have been used on the experimental data on Pu from different kinds of reactors, e.g. research, power reactors with low and high burn-up as well as for fuels with different 235U content. It is demonstrated that the combined use of isotope correlations and PCA is a powerful tool to discriminate Pu originating from different types of reactors. We believe that these studies are valuable for the growing branch of nuclear forensics.